2019
DOI: 10.1002/ame2.12059
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ISCA1 causes early embryonic death in rats

Abstract: Background Iron‐sulfur cluster assembly 1 ( ISCA 1) is an iron‐sulfur (Fe/S) carrier protein that accepts Fe/S from a scaffold protein and transfers it to target proteins including the mitochondrial Fe/S containing proteins. ISCA 1 is also the newly identified causal gene for multiple mitochondrial dysfunctions syndrome ( MMDS ). However, our knowledge about the physiological function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…ISCA1 relocates Fe/S from a scaffold protein to the mitochondrial proteins from the respiratory complex, which is necessary for their stability. It has been reported that ISCA1 knockout led to impairment of the electron transport chain and energy metabolism (Yang et al 2019). Here, following the conditional ITGB3 knockdown, ISCA1 was persistently downregulated, which might be a hint for impeded cellular energy metabolism.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…ISCA1 relocates Fe/S from a scaffold protein to the mitochondrial proteins from the respiratory complex, which is necessary for their stability. It has been reported that ISCA1 knockout led to impairment of the electron transport chain and energy metabolism (Yang et al 2019). Here, following the conditional ITGB3 knockdown, ISCA1 was persistently downregulated, which might be a hint for impeded cellular energy metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…The effects observed following ITGB3 knockdown in vitro and in vivo can be explained by downregulation of specific genes, which have roles in angiogenesis (NPTN, RRM2) (Rodriguez-Pinto et al 2009;Chen et al 2019), tumor growth (NPTN) (Rodriguez-Pinto et al 2009), energy metabolism (ISCA1) (Yang et al 2019), cytokinesis (SEPT11) (Hanai et al 2004), migration (RRM2, STX6) (Chen et al 2019;Zhu et al 2016), cell proliferation, invasiveness, senescence, tumorigenesis (RRM2) (Chen et al 2019) and vesicle trafficking (SEPT11, STX6) (Hanai et al 2004;Zhu et al 2016). It is known that the high expression of neuroplastin (NPTN) in breast carcinomas with distant metastasis is related to a significant increase in tumor growth and angiogenesis (Rodriguez-Pinto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of ISCA1 on organ development, we first established ISCA1 knockout rats by replacing the exon 1 of ISCA1 gene with the mCherry-Cre fusion gene using CRISPR-Cas9 technology in our lab as previously reported [48]. We found that knockout homozygous rats (Isca1 mCherry-Cre -/-) cannot be available in the pups born, which arrested fetal development at E8.5 [48].…”
Section: Myocardial Specific Isca1 Deficiency Induces Severe Hf In Ratsmentioning
confidence: 98%
“…To investigate the effects of ISCA1 on organ development, we first established ISCA1 knockout rats by replacing the exon 1 of ISCA1 gene with the mCherry-Cre fusion gene using CRISPR-Cas9 technology in our lab as previously reported [48]. We found that knockout homozygous rats (Isca1 mCherry-Cre -/-) cannot be available in the pups born, which arrested fetal development at E8.5 [48]. Thus, to further explore how ISCA1 shapes heart morphology and function in vivo, we first established Isca1 conditional knockout (Isca1 cKO) rat in this study (Figure 2A), and selectively eliminated ISCA1 from the α-MHC rat genome by crossing Isca1 cKO rats with the α-MHC-Cre rats (Figure 2B).…”
Section: Myocardial Specific Isca1 Deficiency Induces Severe Hf In Ratsmentioning
confidence: 99%